Stimulatory Effect of Delonix regia Flower Extract in Protecting Syzygium cumini Seedlings from Salinity - Abdullah H. Alayafi; Abeer A. Dahab; Abdel-Nasser A. El-Sheshtawy; Ashutosh Sharma; Abeer Elhakem; Samah M. Youssef; Rasha S. El-Serafy (Plants)
Syzygium cumini (L.) Skeels (jamun) is an ornamental tree species that is sensitive to salinity. Salinity stress is a major challenge, particularly in regions with saline irrigation water. In the present study, the ameliorative potential of foliar application of an aqueous extract of Delonix regia (Poinciana) flowers (PFE) to saline water-irrigated jamun seedlings was investigated over a period of two years. PFE was effective in mitigating the harmful effects of salinity on plant growth, physiology, and biochemistry. Salinity-induced reductions in plant height, leaf area, and biomass which were significantly alleviated by PFE foliar application. The extract also enhanced antioxidant activity, as indicated by increased ferric reducing antioxidant potential (FRAP) and phenolic content, while also reducing hydrogen peroxide (H2O2) levels and membrane damage as indicated by the accumulation of malondialdehyde (MDA). Additionally, the foliar application of PFE promoted the accumulation of free proline, an essential osmo-protectant, further enhancing the plant’s resilience to salinity stress. These findings highlight the potential of PFE as an eco-friendly bio-stimulant to improve salinity tolerance in jamun and pave the way for sustainable salinity management strategies in other crops as well.